A qualitative approach to examining antimicrobial prescribing in the outpatient dental setting. Issue 1 (24th June 2022) - Hughes, Ashley M.; Evans, Charlesnika T.; Fitzpatrick, Margaret A.; Kale, Ibuola O.; Vivo, Amanda; Boyer, Taylor L.; Solanki, Pooja A.; Gibson, Gretchen; Jurasic, M. Marianne; Sharp, Lisa K.; Echevarria, Kelly L.; Suda, Katie J.
Abstract: Objective: To understand barriers and facilitators to evidence-based prescribing of antibiotics in the outpatient dental setting. Design: Semistructured interviews. Setting: Outpatient dental setting. Participants: Dentists from 40 Veterans' Health Administration (VA) facilities across the United States. Methods: Dentists were identified based on their prescribing patterns and were recruited to participate in a semistructured interview on perceptions toward prescribing. All interviews were recorded, transcribed, and double-coded for analysis, with high reliability between coders. We identified general trends using the theoretical domains framework and mapped overarching themes onto the behavior change wheel to identify prospective interventions that improve evidence-based prescribing. Results: In total, 90 dentists participated in our study. The following barriers and facilitators to evidence-based prescribing emerged as impacts on a dentist's decision making on prescribing an antibiotic: access to resources, social influence of peers and other care providers, clinical judgment, beliefs about consequences, local features of the clinic setting, and beliefs about capabilities. Conclusions: Findings from this work reveal the need to increase awareness of up-to-date antibiotic prescribing behaviors in dentistry and may inform the best antimicrobial stewardship interventions to support dentists' ongoing professional development and improve evidence-based prescribing.